Comparison Some Parametric and Non –parametric Methods To Estimate Median Effective Dose ( ED5 - احمد, ايمان حسن; عبد الوهاب, عمر عادل (Journal of Economics and Administrative Sciences, 2013)
In this paper the research represents an attempt of expansion in using the parametric and non-parametric estimators to estimate the median effective dose ( ED50 ) in the quintal bioassay and comparing between  these methods . We have Chosen three estimators for Comparison. The first estimator is ( Spearman-Karber )  and the second estimator is ( Moving Average ) and The Third estimator  is ( Extreme Effective Dose ) . We used a minimize Chi-square as a parametric method. We made a Comparison for these estimators by calculating the mean square error of (ED50) for each one of them and comparing it with the optimal the mean square error of ( ED50 ) and conclude results and finally this paper show that a parametric method ( minimize Chi-square ) is better than a non-parametric methods .